2020
DOI: 10.1007/s10661-020-08697-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen stocks and flows in an acid sulfate soil

Abstract: Besides causing acidification, acid sulfate (AS) soils contain large nitrogen (N) stocks and are a potential source of N loading to waters and nitrous oxide (N2O) emissions. We quantified the stocks and flows of N, including crop yields, N leaching, and N2O emissions, in a cultivated AS soil in western Finland. We also investigated whether controlled drainage (CD) and sub-irrigation (CDI) to keep the sulfidic horizons inundated can alleviate N losses. Total N stock at 0–100 cm (19.5 Mg ha−1) was smaller than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Slightly higher bulk density, pH and NO 3 − -N content in the non-AS soil compared with AS soil may have contributed to this exception, even if the underlying reasons remain uncertain and a possible topic of future research. Nevertheless, our results are generally in agreement with recent studies that have indicated larger N 2 O emissions from AS soil than from non-AS mineral soils in Finland (Šimek et al, 2011;Šimek et al, 2014;Yli-Halla et al, 2020) and Australia (Galbally et al, 2010;Macdonald et al, 2008). Our results support the view that NO 3 − -N and NH 4 + -N were important factors affecting oxic N 2 O production and emissions from AS soils through nitrification and denitrification.…”
Section: Effects Of Liming On the Oxic Production Of N 2 Osupporting
confidence: 93%
See 1 more Smart Citation
“…Slightly higher bulk density, pH and NO 3 − -N content in the non-AS soil compared with AS soil may have contributed to this exception, even if the underlying reasons remain uncertain and a possible topic of future research. Nevertheless, our results are generally in agreement with recent studies that have indicated larger N 2 O emissions from AS soil than from non-AS mineral soils in Finland (Šimek et al, 2011;Šimek et al, 2014;Yli-Halla et al, 2020) and Australia (Galbally et al, 2010;Macdonald et al, 2008). Our results support the view that NO 3 − -N and NH 4 + -N were important factors affecting oxic N 2 O production and emissions from AS soils through nitrification and denitrification.…”
Section: Effects Of Liming On the Oxic Production Of N 2 Osupporting
confidence: 93%
“…In the Ap1 and Bg1 horizons of the AS soil, the initial large amounts of NO 3 − -N (27.8 mg kg −1 in the Ap1 and 7.7 mg kg −1 in the Bg1) may have originated from the mineralization of soil organic matter and nitrification (Yli-Halla et al, 2020). The decreasing N 2 O production rate in all horizons and treatments of the AS soil over time during Phase Oxic I was probably due to the gradual depletion of NO 3 − -N. We attributed this decrease in NO 3 − -N content in the Ap1 and Bg1 horizons to denitrification within anaerobic microsites of soil aggregates, which have been demonstrated to occur frequently, even in apparently oxic soils (Stevens et al, 1997), and to the immobilization of N (Case et al, 2015) into the microbial biomass, as there was no leaching from the incubation vessels.…”
Section: Effects Of Liming On the Oxic Production Of N 2 Omentioning
confidence: 99%
“…5). Over a seven-year period, the monitoring of mineral AS soil in western Finland revealed that an average of 55 kg N ha -1 was leached annually through the subsurface drainage system (Yli- Halla et al, 2020), whereas the national average leached from agricultural land is approximately 15 kg N ha -1. In this particular field, the N contained in the harvested crop plus the N contained in the discharge made up 148% of the N fertilization.…”
Section: Nitrogen Content Of the Acid Sulfate Soilsmentioning
confidence: 99%
“…+ and concentrated just below the peat layer (Yli-Halla et al, 2017). AS soils are shown to have large GHG emissions: Denmead et al (2010), in studying CH 4 and N 2 O, detected tenfold emissions (expressed as CO 2 equivalent) compared to those from non-AS soils under sugarcane cultivation in Australia, and unusually high fluxes of N 2 O, annually 2-28 kg N ha − 1 , have been observed in a coastal mineral AS soil in Finland (Uusi-Kämppä et al, 2012;Yli-Halla et al, 2020). Šimek et.…”
Section: Introductionmentioning
confidence: 99%